2015
DOI: 10.3109/15622975.2015.1091502
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style and oxytocin receptor gene variation interact in influencing social anxiety

Abstract: The present pilot data point to a strong association of less secure attachment and social anxiety as well as to a gene-environment interaction effect of OXTR rs53576 genotype and attachment style on social anxiety possibly constituting a targetable combined risk marker of social anxiety disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 46 publications
3
23
0
1
Order By: Relevance
“…Veterans with insecure attachment were at significantly higher risk of meeting screening criteria for PTSD if they had at least one rs53576*A compared to G homozygotes. This finding parallels results showing that insecurely attached individuals with an A allele were more socially anxious than G homozygotes (Notzon et al, 2016), and that OXTR rs53575 genotype interacted with negative social environments to predict PTSD symptoms (Lucas-Thompson and Holman, 2013). Further, the association between insecure attachment style and greater likelihood of probable PTSD is consistent with longitudinal observations of the effect of insecure attachment on PTSD symptoms (Franz et al, 2014) and extends previous findings in military samples (Currier et al, 2012; Escolas et al, 2012) to a nationally representative sample, and is clinically relevant given that an insecure attachment style has been linked to reduced treatment response among veterans with PTSD (Forbes et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Veterans with insecure attachment were at significantly higher risk of meeting screening criteria for PTSD if they had at least one rs53576*A compared to G homozygotes. This finding parallels results showing that insecurely attached individuals with an A allele were more socially anxious than G homozygotes (Notzon et al, 2016), and that OXTR rs53575 genotype interacted with negative social environments to predict PTSD symptoms (Lucas-Thompson and Holman, 2013). Further, the association between insecure attachment style and greater likelihood of probable PTSD is consistent with longitudinal observations of the effect of insecure attachment on PTSD symptoms (Franz et al, 2014) and extends previous findings in military samples (Currier et al, 2012; Escolas et al, 2012) to a nationally representative sample, and is clinically relevant given that an insecure attachment style has been linked to reduced treatment response among veterans with PTSD (Forbes et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…The OXTR SNP rs53576 has previously been found to interact with attachment style to predict social anxiety; individuals with an A allele and less secure attachment reported more social anxiety than G homozygotes (Notzon et al, 2016). In the only published study of OXTR rs53576 genotype and PTSD symptoms, among individuals with an A allele, a perceived negative social environment was associated with significantly increased PTSD symptoms (regardless of economic stress), while among G homozygotes, a negative social environment predicted elevated PTSD symptoms only for individuals reporting high economic stress (Lucas-Thompson and Holman, 2013).…”
mentioning
confidence: 99%
“…To the best of our knowledge, there was only one study with inverse results, reporting that the A allele did not have a protective effect. Specifically, there was a stronger negative effect of a less secure attachment style on social anxiety among A allele carriers ( Notzon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…This contrasts with our previous finding in individuals with SAD that oxytocin’s effect on social cooperation was most potent for those who were low in attachment avoidance (Fang et al, 2014). Future research should examine the attachment-dependent effects of oxytocin on social cognition in SAD, as a recent study found a strong association between the oxytocin receptor genotype (rs53576) and insecure attachment among healthy individuals at risk for social anxiety (Notzon et al, 2016). …”
Section: Discussionmentioning
confidence: 99%